Managing factory floor data. (Manufacturing Engineering)
As manufacturers wrestle with global competition and the constant need to cut costs, manufacturing operations seek the most efficient software tools to monitor and manage often far flung factory facilities. Advances in ERP and MES software, including cloud-based systems, can help manufacturers control critical manufacturing operations.